A low-density high-flame-retardant EPDM rubber composite material and preparation method thereof
By using appropriate accelerators and synergistic flame retardant components in EPDM rubber and plastic foaming, the problem of mismatch between vulcanization speed and foaming speed is solved, and low-density, high-flame retardant composite materials are prepared. The fine cell and flame retardant performance have been improved, and the problem of poor flame retardant performance of EPDM rubber-plastic composite materials in the prior art has been solved.
Patent Information
- Application Number
- CN202411247546.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-06
Smart Images

Figure CN118772545B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of materials, and in particular to a low-density high-flame-retardant EPDM rubber composite material and a preparation method thereof. Background Art
[0002] Rubber-plastic foam products have fine, independent, closed cells that can effectively prevent the spread of heat, thus having good thermal insulation performance. Currently, rubber-plastic insulation materials on the market are mainly divided into three categories according to the type of rubber: nitrile rubber-plastic foam, EPDM rubber-plastic foam, and diene rubber-plastic foam. Among them, nitrile is the most common and widely used, but nitrile rubber-plastic foam has poor high temperature resistance, especially poor anti-aging performance, which greatly limits the application of nitrile rubber-plastic foam.
[0003] EPDM has excellent weather resistance because its main chain is composed of saturated bonds. It can also be used for a long time at 150°C, which largely makes up for the defects of nitrile rubber and plastic. However, since the main chain of EPDM is a saturated structure, the vulcanization speed is slow when preparing foam products. There is often a mismatch between the vulcanization speed and the foaming speed, which makes it difficult to prepare low-density and small-cell EPDM rubber and plastic. This is also the main reason why there are few EPDM rubber and plastic insulation products on the market. In addition, EPDM itself has poor flame retardant properties, and it is even more difficult to prepare EPDM rubber and plastic foam with high flame retardant properties. Summary of the invention
[0004] In order to solve the problems mentioned in the background technology, the object of the present invention is to provide a low-density and highly flame-retardant EPDM rubber composite material and a preparation method thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A method for preparing a low-density and highly flame-retardant EPDM rubber composite material, wherein the composite material is prepared from the following raw materials in parts by weight: 50-80 parts of EPDM rubber, 40-60 parts of talc, 50-70 parts of sponge powder, 50-80 parts of chlorinated paraffin oil, 20-50 parts of azodicarbonamide, 3-6 parts of synergistic flame retardant components, 3-5 parts of zinc oxide, 5-15 parts of aluminum hydroxide, 8-20 parts of calcium carbonate, 0.8-3 parts of dispersant, 2-3 parts of polyethylene glycol, 10-15 parts of carbon black, 10-30 parts of polyethylene wax, 1-2 parts of vulcanization accelerator PZ, 0.3-1 parts of sulfur, 0.8-2 parts of accelerator DPTT, and 1-2 parts of vulcanization accelerator EZ;
[0007] The preparation method comprises the following steps:
[0008] The first step is to add EPDM rubber, talcum powder, sponge powder, chlorinated paraffin oil, azodicarbonamide, synergistic flame retardant components, zinc oxide, aluminum hydroxide, calcium carbonate, dispersant, polyethylene glycol, carbon black, and polyethylene wax into an internal mixer, mix at 130-140°C, mix evenly, transfer to a cutting machine for rolling into sheets, and after the rubber material is cooled, leave it for 36-48 hours to form a pre-treated material;
[0009] The second step is to add the vulcanization accelerator PZ, sulfur, accelerator DPTT and vulcanization accelerator EZ into the pretreated material by means of secondary open milling. After mixing evenly, cool for 10-20 minutes, add to the extruder for extrusion, control the head temperature at 50-60°C, and the extruded rubber material is sequentially passed through six sections of drying tunnels with different temperatures for vulcanization and foaming. The drying tunnel temperatures are 135±2°C, 143±2°C, 158±2°C, 170±2°C, 185±2°C and 193±2°C respectively. After leaving the drying tunnel, it is cooled by air cooling and then packed in bags to obtain the EPDM rubber composite material.
[0010] In the above technical scheme, PZ and EZ are ultra-fast accelerators. With the increase of the dosage of PZ and EZ, the vulcanization speed increases significantly. When the dosage of sulfur and DPTT is increased, the vulcanization speed is further accelerated. However, when the dosage of sulfur is too large, reflux will occur. In addition, the wall of the rubber and plastic foaming pores will become thicker, and the overall density and strength will increase. Therefore, the present invention selects the appropriate type and dosage of accelerators to make the prepared composite material have uniform pores.
[0011] As a further embodiment of the present invention, the preparation method of the synergistic flame retardant component comprises the following steps:
[0012] Step A, adding gelatin to dimethyl sulfoxide, stirring and mixing until a uniform liquid is formed, and then adding 3-tert-butyldimethylsilyloxyglutaric anhydride to the liquid under ice bath conditions, after the addition is complete, removing the ice bath, stirring at room temperature for 2-4 hours, discharging the material, and obtaining a flame retardant precursor;
[0013] Step B: add the flame retardant precursor to toluene, stir and mix evenly, then add the hydroxyl-substituted phosphorus-containing flame retardant and the phase transfer catalyst. After the addition, gradually increase the temperature to 90-100°C and continue stirring for 3-6 hours, stop heating, cool and discharge the material to obtain a synergistic flame retardant component.
[0014] As a further embodiment of the present invention, in step A, the mass ratio of gelatin to 3-tert-butyldimethylsilyloxyglutaric anhydride is 1:0.1-0.2.
[0015] As a further embodiment of the present invention, in step B, the hydroxyl-substituted phosphorus-containing flame retardant is flame retardant FRC-6 or pentaerythritol phosphate.
[0016] As a further embodiment of the present invention, in step B, the phase transfer catalyst is trifluoromethanesulfonic acid or p-toluenesulfonic acid.
[0017] In the above technical scheme, gelatin is first modified with 3-tert-butyldimethylsilyloxyglutaric anhydride to obtain a gelatin derivative containing a carboxyl substituent, i.e., a flame retardant precursor. Then, under the action of a phase transfer catalyst, a hydroxyl-substituted phosphorus-containing flame retardant is used to further condense the active carboxyl substituents in the flame retardant precursor structure to obtain a synergistic flame retardant component having a structure containing ternary composite flame retardant elements of silicon, nitrogen and phosphorus.
[0018] A low-density and highly flame-retardant EPDM rubber composite material is prepared by adopting the preparation method.
[0019] Beneficial effects of the present invention:
[0020] (1) Since the main chain of EPDM is a saturated hydrocarbon structure, it is difficult to vulcanize with sulfur. When using sulfur for vulcanization, EPDM with more unsaturated bonds in the side chain must be selected. Even so, it is still difficult to match the decomposition rate of AC foaming agent with the vulcanization rate of EPDM rubber with sulfur alone. Therefore, the present invention adopts the selection of appropriate accelerator types and accelerator dosages to solve the problem that the vulcanization rate of EPDM rubber and plastic foaming is difficult to match the foaming rate, and the prepared composite material has a small foaming density and fine pores. The amount of PZ is extremely important for the regulation of the vulcanization rate and the influence of the pore structure. When the amount of PZ is low, the vulcanization rate is lower than the foaming rate, the rubber and plastic pores are too large, and even the pores are broken, and the gas overflows, resulting in insufficient foaming ratio and rough rubber and plastic surface. However, when PZ is excessive, the rubber vulcanization is too fast, resulting in insufficient number of pores and hardening of the rubber and plastic.
[0021] (2) The synergistic flame retardant component prepared by the present invention uses gelatin as a carbonizing agent, and the nitrogen element in its structure as a gas source, and is combined with the acid source provided by the phosphate compound to form a ternary expansion synergistic flame retardant. This synergistic flame retardant has a strong flame retardant effect and can quickly form an expansion carbon layer when the material burns. The silicon element in its structure will form high-strength silicon oxide, which adheres to the surface of the carbon layer to prevent continued combustion. Combined with the inorganic flame retardant aluminum hydroxide, the flame retardant performance of the material can reach B1 level. Moreover, the addition of the synergistic flame retardant can greatly reduce the amount of inorganic flame retardant added, thereby avoiding the problem that excessive addition of inorganic flame retardant has a negative impact on material strength.
[0022] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0024] Figure 1 This is a graph showing the vulcanization characteristics of the composite materials in Examples 1 to 4 of the present invention. DETAILED DESCRIPTION
[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Preparation Example 1
[0027] Preparation of synergistic flame retardant components:
[0028] Step A, adding 1.5 g of gelatin to dimethyl sulfoxide, stirring and mixing until a uniform liquid is formed, and then adding 0.2 g of 3-tert-butyldimethylsilyloxyglutaric anhydride to the liquid under ice bath conditions, after the addition is complete, removing the ice bath, stirring at room temperature for 3 hours, discharging the material, and obtaining a flame retardant precursor;
[0029] Step B, add 1.2g of flame retardant precursor to toluene, stir and mix evenly, then add 0.3g of pentaerythritol phosphate and 0.05g of p-toluenesulfonic acid. After the addition, gradually increase the temperature to 90-100°C and continue stirring for 3-6h, stop heating, cool and discharge the material to obtain a synergistic flame retardant component.
[0030] Example 1
[0031] A low-density and highly flame-retardant EPDM rubber composite material is prepared from the following raw materials in parts by weight: 50 parts of EPDM rubber, 40 parts of talc, 50 parts of sponge powder, 80 parts of chlorinated paraffin oil, 20 parts of azodicarbonamide, 3 parts of synergistic flame retardant components, 3 parts of zinc oxide, 5 parts of aluminum hydroxide, 8 parts of calcium carbonate, 0.8 parts of saturated fatty acid zinc salt dispersant LP623A, 2 parts of polyethylene glycol, 10 parts of carbon black, 10 parts of polyethylene wax, 1 part of vulcanization accelerator PZ, 0.3 parts of sulfur, 0.8 parts of accelerator DPTT, and 1 part of vulcanization accelerator EZ;
[0032] The preparation method of the composite material comprises the following steps:
[0033] The first step is to add EPDM rubber, talcum powder, sponge powder, chlorinated paraffin oil, azodicarbonamide, synergistic flame retardant components, zinc oxide, aluminum hydroxide, calcium carbonate, saturated fatty acid zinc salt dispersant LP623A, polyethylene glycol, carbon black, and polyethylene wax into an internal mixer, mix at 130°C, mix evenly, transfer to a material cutter for rolling into sheets, and after the rubber material is cooled, leave it for 48 hours to form a pre-treated material;
[0034] In the second step, vulcanization accelerator PZ, sulfur, accelerator DPTT and vulcanization accelerator EZ are added to the pretreated material by means of secondary open milling. After being mixed evenly, the mixture is cooled for 10 minutes and then added to the extruder for extrusion. The head temperature is controlled at 50°C. The extruded rubber material is sequentially passed through six drying ovens with different temperatures for vulcanization and foaming. The drying oven temperatures are 135±2°C, 143±2°C, 158±2°C, 170±2°C, 185±2°C and 193±2°C respectively. After exiting the drying oven, the rubber material is cooled by air cooling and then packed in bags to obtain the EPDM rubber composite material.
[0035] Example 2
[0036] A low-density and highly flame-retardant EPDM rubber composite material is prepared from the following raw materials in parts by weight: 50 parts of EPDM rubber, 50 parts of talc, 50 parts of sponge powder, 68 parts of chlorinated paraffin oil, 35 parts of azodicarbonamide, 5 parts of synergistic flame retardant components, 3 parts of zinc oxide, 8 parts of aluminum hydroxide, 20 parts of calcium carbonate, 0.8 parts of saturated fatty acid zinc salt dispersant LP623A dispersant, 2 parts of polyethylene glycol, 10 parts of carbon black, 15 parts of polyethylene wax, 1 part of vulcanization accelerator PZ, 1 part of sulfur, 0.8 parts of accelerator DPTT, and 1 part of vulcanization accelerator EZ;
[0037] The preparation method of the composite material comprises the following steps:
[0038] The first step is to add EPDM rubber, talcum powder, sponge powder, chlorinated paraffin oil, azodicarbonamide, synergistic flame retardant components, zinc oxide, aluminum hydroxide, calcium carbonate, saturated fatty acid zinc salt dispersant LP623A, polyethylene glycol, carbon black, and polyethylene wax into an internal mixer, mix at 140°C, mix evenly, transfer to a material cutter for rolling into sheets, and after the rubber material is cooled, leave it for 48 hours to form a pre-treated material;
[0039] In the second step, vulcanization accelerator PZ, sulfur, accelerator DPTT and vulcanization accelerator EZ are added to the pretreated material by means of secondary open milling. After being mixed evenly, the mixture is cooled for 20 minutes and then added to the extruder for extrusion. The head temperature is controlled at 60°C. The extruded rubber material is sequentially passed through six drying ovens with different temperatures for vulcanization and foaming. The drying oven temperatures are 135±2°C, 143±2°C, 158±2°C, 170±2°C, 185±2°C and 193±2°C respectively. After exiting the drying oven, the rubber material is cooled by air cooling and then packed in bags to obtain the EPDM rubber composite material.
[0040] Example 3
[0041] A low-density and highly flame-retardant EPDM rubber composite material is prepared from the following raw materials in parts by weight: 65 parts of EPDM rubber, 60 parts of talc, 60 parts of sponge powder, 68 parts of chlorinated paraffin oil, 40 parts of azodicarbonamide, 5 parts of synergistic flame retardant components, 5 parts of zinc oxide, 10 parts of aluminum hydroxide, 8 parts of calcium carbonate, 1.5 parts of saturated fatty acid zinc salt dispersant LP623A, 3 parts of polyethylene glycol, 15 parts of carbon black, 21 parts of polyethylene wax, 1.5 parts of vulcanization accelerator PZ, 0.8 parts of sulfur, 1.5 parts of accelerator DPTT, and 2 parts of vulcanization accelerator EZ;
[0042] The preparation method of the composite material comprises the following steps:
[0043] The first step is to add EPDM rubber, talcum powder, sponge powder, chlorinated paraffin oil, azodicarbonamide, synergistic flame retardant components, zinc oxide, aluminum hydroxide, calcium carbonate, saturated fatty acid zinc salt dispersant LP623A, polyethylene glycol, carbon black, and polyethylene wax into an internal mixer, mix at 140°C, mix evenly, transfer to a material cutter for rolling into sheets, and after the rubber material is cooled, leave it for 48 hours to form a pre-treated material;
[0044] In the second step, vulcanization accelerator PZ, sulfur, accelerator DPTT and vulcanization accelerator EZ are added to the pretreated material by means of secondary open milling. After being mixed evenly, the mixture is cooled for 20 minutes and then added to the extruder for extrusion. The head temperature is controlled at 60°C. The extruded rubber material is sequentially passed through six drying ovens with different temperatures for vulcanization and foaming. The drying oven temperatures are 135±2°C, 143±2°C, 158±2°C, 170±2°C, 185±2°C and 193±2°C respectively. After exiting the drying oven, the rubber material is cooled by air cooling and then packed in bags to obtain the EPDM rubber composite material.
[0045] Example 4
[0046] A low-density and highly flame-retardant EPDM rubber composite material, which is prepared from the following raw materials in parts by weight: 80 parts of EPDM rubber, 60 parts of talc, 70 parts of sponge powder, 50 parts of chlorinated paraffin oil, 50 parts of azodicarbonamide, 6 parts of synergistic flame retardant components, 5 parts of zinc oxide, 15 parts of aluminum hydroxide, 8 parts of calcium carbonate, 3 parts of dispersant, 3 parts of polyethylene glycol, 15 parts of carbon black, 30 parts of polyethylene wax, 2 parts of vulcanization accelerator PZ, 1 part of sulfur, 2 parts of accelerator DPTT, and 2 parts of vulcanization accelerator EZ;
[0047] The preparation method of the composite material comprises the following steps:
[0048] The first step is to add EPDM rubber, talcum powder, sponge powder, chlorinated paraffin oil, azodicarbonamide, synergistic flame retardant components, zinc oxide, aluminum hydroxide, calcium carbonate, saturated fatty acid zinc salt dispersant LP623A, polyethylene glycol, carbon black, and polyethylene wax into an internal mixer, mix at 140°C, mix evenly, transfer to a material cutter for rolling into sheets, and after the rubber material is cooled, leave it for 48 hours to form a pre-treated material;
[0049] In the second step, vulcanization accelerator PZ, sulfur, accelerator DPTT and vulcanization accelerator EZ are added to the pretreated material by means of secondary open milling. After being mixed evenly, the mixture is cooled for 20 minutes and then added to the extruder for extrusion. The head temperature is controlled at 60°C. The extruded rubber material is sequentially passed through six drying ovens with different temperatures for vulcanization and foaming. The drying oven temperatures are 135±2°C, 143±2°C, 158±2°C, 170±2°C, 185±2°C and 193±2°C respectively. After exiting the drying oven, the rubber material is cooled by air cooling and then packed in bags to obtain the EPDM rubber composite material.
[0050] Comparative Example 1
[0051] A low-density and highly flame-retardant EPDM rubber composite material, which is different from Example 2 in that the synergistic flame-retardant component is removed and the rest remains unchanged.
[0052] Test Case
[0053] a. The composite materials in Examples 1 to 4 and Comparative Example 1 were tested for performance, and the results are shown in the following table:
[0054]
[0055] Note: The limiting oxygen index test is carried out in accordance with the reference standard GB / T 2406.2-2009; the Mooney viscosity test adopts a rotor Mooney viscometer, and the test conditions are 100℃ and 4min.
[0056] It can be seen from the test results that the composite materials prepared by adding synergistic flame retardant components in Examples 1 to 4 of the present invention have excellent flame retardant properties and a high Mooney viscosity, which is conducive to the composite materials forming a flat and smooth surface and having fine and uniform bubbles.
[0057] After the synergistic flame retardant component was removed in Comparative Example 1, the limiting oxygen index was greatly reduced. This was because the synergistic flame retardant component could not be used to form an expanded carbon layer, making it difficult to prevent the continued combustion.
[0058] b. According to the standard GB / T 9869-1997, the vulcanization characteristics of the composite materials of Examples 1 to 4 were tested. The results are shown in Figure 1 A1, A2, A3, and A4 represent the vulcanization curves of the composite materials in Examples 1 to 4, respectively, and B1, B2, B3, and B4 represent the foaming curves of the composite materials in Examples 1 to 4, respectively.
[0059] from Figure 1 It can be analyzed that through testing, it can be found that under the test conditions of 170℃ and 4min, the vulcanization speed increases significantly with the increase of PZ and DPTT. When the amount of PZ and DPTT increases to 2 parts, the vulcanization curve and foaming curve of the rubber and plastic basically match (curve 4 in the figure). Under this condition, we can obtain EPDM rubber-plastic foamed composite materials with fine and uniform pores, low density and high foaming ratio.
[0060] Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enable any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.
[0061] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a low-density, highly flame-retardant EPDM rubber composite material, characterized in that: The composite material is made of the following raw materials in parts by weight: 50-80 parts of EPDM rubber, 40-60 parts of talc, 50-70 parts of sponge powder, 50-80 parts of chlorinated paraffin oil, 20-50 parts of azodicarbonamide, 3-6 parts of synergistic flame retardant components, 3-5 parts of zinc oxide, 5-15 parts of aluminum hydroxide, 8-20 parts of calcium carbonate, 0.8-3 parts of dispersant, 2-3 parts of polyethylene glycol, 10-15 parts of carbon black, 10-30 parts of polyethylene wax, 1-2 parts of vulcanization accelerator PZ, 0.3-1 parts of sulfur, 0.8-2 parts of accelerator DPTT, and 1-2 parts of vulcanization accelerator EZ. The preparation method comprises the following steps: The first step is to add EPDM rubber, talcum powder, sponge powder, chlorinated paraffin oil, azodicarbonamide, synergistic flame retardant components, zinc oxide, aluminum hydroxide, calcium carbonate, dispersant, polyethylene glycol, carbon black, and polyethylene wax into an internal mixer, mix at 130-140°C, mix evenly, transfer to a cutting machine for rolling into sheets, and after the rubber material is cooled, leave it for 36-48 hours to form a pre-treated material; The second step is to add the vulcanization accelerator PZ, sulfur, accelerator DPTT and vulcanization accelerator EZ to the pretreated material in a secondary open milling manner, mix well, cool for 10-20 minutes, add to the extruder for extrusion, control the head temperature at 50-60°C, and the extruded rubber material is sequentially passed through six sections of drying tunnels with different temperatures for vulcanization and foaming. The drying tunnel temperatures are 135±2°C, 143±2°C, 158±2°C, 170±2°C, 185±2°C and 193±2°C respectively. After exiting the drying tunnel, it is cooled by air cooling and then packaged to obtain an EPDM rubber composite material; The preparation method of the synergistic flame retardant component comprises the following steps: Step A, adding gelatin to dimethyl sulfoxide, stirring and mixing until a uniform liquid is formed, and then adding 3-tert-butyldimethylsilyloxyglutaric anhydride to the liquid under ice bath conditions, after the addition is complete, removing the ice bath, stirring at room temperature for 2-4 hours, discharging the material, and obtaining a flame retardant precursor; Step B: add the flame retardant precursor to toluene, stir and mix evenly, then add the hydroxyl-substituted phosphorus-containing flame retardant and the phase transfer catalyst. After the addition, gradually increase the temperature to 90-100°C and continue stirring for 3-6 hours, stop heating, cool and discharge the material to obtain a synergistic flame retardant component.
2. The method for preparing a low-density and highly flame-retardant EPDM rubber composite material according to claim 1, characterized in that: In step A, the mass ratio of gelatin to 3-tert-butyldimethylsilyloxyglutaric anhydride is 1:0.1-0.
2.
3. The method for preparing a low-density and highly flame-retardant EPDM rubber composite material according to claim 1, characterized in that: In step B, the hydroxyl-substituted phosphorus-containing flame retardant is flame retardant FRC-6 or pentaerythritol phosphate.
4. The method for preparing a low-density and highly flame-retardant EPDM rubber composite material according to claim 1, characterized in that: In step B, the phase transfer catalyst is trifluoromethanesulfonic acid or p-toluenesulfonic acid.
5. A low-density, highly flame-retardant EPDM rubber composite material, characterized in that: The method is prepared according to claim 1.
Citation Information
Patent Citations
Low-density ethylene propylene diene monomer extruded sponge material and preparation method thereof
CN111320821A
Low-density foaming expansion flame-retardant ethylene propylene rubber and preparation method thereof
CN111647233A
Cited By
Method for enhancing thermal stability and oxidation stability of EPDM (ethylene propylene diene monomer) rubber by using functionalized h-BN (boron nitride) nanosheets
CN119912756A
A method for enhancing thermal stability and oxidative stability of ethylene propylene diene rubber by functionalized h-bn nanosheets
CN119912756B